2021
DOI: 10.1089/thy.2020.0044
|View full text |Cite
|
Sign up to set email alerts
|

Mice Hypomorphic forKeap1, a Negative Regulator of the Nrf2 Antioxidant Response, Show Age-Dependent Diffuse Goiter with Elevated Thyrotropin Levels

Abstract: Background: Familial nontoxic multinodular goiter (MNG) is a rare disease. One of the associated genes is Kelch-like ECH-associated protein 1 ( KEAP1 ), which encodes the main inhibitor of nuclear factor erythroid 2-related transcription factor 2 (Nrf2), a central mediator of antioxidant responses. The association of KEAP1 with familial MNG is based on only two loss-of-function mutations identified in two families, only one of which included proper phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…In studies using Nrf2 KO mice, mice with tissue-restricted deletion of Nrf2 (using Pax8-Cre recombinase that is expressed primarily in the thyroid and the kidney), and thyroid follicular cell lines with inactivated Nrf2 or Keap1 (using the CRISPR/Cas9 method), we showed that Nrf2 activity correlated positively with the mRNA expression levels of antioxidant and/or selenoprotein genes such as Nqo1 (NAD(P)H quinone dehydrogenase 1), Gpx2 (glutathione peroxidase 2), and Txnrd1 (thioredoxin reductase 1), as well as with the protein levels of Nqo1 and selenoprotein S (SelS) [2]. More recently, we confirmed this further by demonstrating increased mRNA expression levels of Nqo1, Gpx2 and Txnrd1 as well as increased protein abundance of Nqo1 in the thyroids of Keap1 KD mice [24]. We also showed that the antioxidant function of Nrf2 is triggered by exposure to supraphysiological amounts of iodide, in order to protect thyroid follicular cells from OS [2].…”
Section: Thyroid Physiologysupporting
confidence: 66%
See 1 more Smart Citation
“…In studies using Nrf2 KO mice, mice with tissue-restricted deletion of Nrf2 (using Pax8-Cre recombinase that is expressed primarily in the thyroid and the kidney), and thyroid follicular cell lines with inactivated Nrf2 or Keap1 (using the CRISPR/Cas9 method), we showed that Nrf2 activity correlated positively with the mRNA expression levels of antioxidant and/or selenoprotein genes such as Nqo1 (NAD(P)H quinone dehydrogenase 1), Gpx2 (glutathione peroxidase 2), and Txnrd1 (thioredoxin reductase 1), as well as with the protein levels of Nqo1 and selenoprotein S (SelS) [2]. More recently, we confirmed this further by demonstrating increased mRNA expression levels of Nqo1, Gpx2 and Txnrd1 as well as increased protein abundance of Nqo1 in the thyroids of Keap1 KD mice [24]. We also showed that the antioxidant function of Nrf2 is triggered by exposure to supraphysiological amounts of iodide, in order to protect thyroid follicular cells from OS [2].…”
Section: Thyroid Physiologysupporting
confidence: 66%
“…Therefore, in a recent study we used Keap1 KD mice to verify whether decreased Keap1 levels can cause goiter. We found that Keap1 KD mice showed a diffuse goiter that was already detectable in early adult life and became more prominent and fully penetrant in later life [24]. Histomorphometric analysis of the thyroids showed that the goiter was characterized by markedly dilated thyroid follicles, and especially an increased size of the colloid compartment, while there were no thyroid nodules or hyperplasia.…”
Section: Subclinical Hypothyroidism and Goitermentioning
confidence: 73%
“…Specifically, under normal conditions (mice not treated with iodide), Nrf2 appears to regulate the expression of cytoprotective and antioxidant genes as is highlighted by the downregulation of the relevant pathways in the thyroids of Nrf2 KO mice ( Figure 4 A) and the lower expression levels of the Nrf2 target genes Nqo1 and Gpx2 ( Figure 3 B). This cytoprotective role of Nrf2 has been well documented in several other tissues, such as the liver [ 36 ]; by using Nrf2 loss- and gain-of-function mouse models, we recently showed that regulation of antioxidant genes by Nrf2 also occurs in the thyroid [ 2 , 37 ]. In these studies, roles of Nrf2 in thyroid economy beyond cytoprotection were also investigated, showing that Nrf2 is a positive regulator of Tg transcription and Tg protein abundance [ 2 ], as well as a negative regulator of Tg iodination [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, roles of Nrf2 in thyroid economy beyond cytoprotection were also investigated, showing that Nrf2 is a positive regulator of Tg transcription and Tg protein abundance [ 2 ], as well as a negative regulator of Tg iodination [ 2 ]. We also showed that decreased expression of Keap1 , which is associated with constitutive activation of Nrf2 signaling, can cause goiter with a tendency for hypothyroidism [ 37 ]. Identification of the full spectrum of Nrf2-regulated genes in the thyroid is important as a basis to further elucidate the mechanism underlying the aforementioned observations.…”
Section: Discussionmentioning
confidence: 99%
“…and broader topic (e.g., neurodegeneration, liver, kidney, lung or cardiovascular disease, cancer, etc.). The particular interest of our group in Nrf2 relates to thyroid physiology and disease [ 44 ]; in that regard, we have previously shown that (i) Nrf2 regulates the expression of thyroglobulin, the precursor of thyroid hormones [ 45 , 46 ]; (ii) constitutive genetic activation of Nrf2 causes thyroid enlargement (goiter) and mild hypothyroidism [ 47 ]; (iii) excess iodide exposure induces inflammatory, fibrosis, and autoimmune pathways along with Nrf2 signaling in the thyroid, which are accentuated by the absence of Nrf2 [ 48 ]; (iv) genetic variation in the NFE2L2 promoter interacts with genetic variation in the promoter of a selenoprotein-encoding gene ( SELENOS ) to modulate the risk of autoimmune thyroiditis (Hashimoto’s disease) [ 49 ]; and (v) clinical use of the Nrf2 pathway activator sulforaphane is safe for thyroid hormonal and autoimmune status in humans [ 50 ]. Therefore, among the various topics emerging from the Nrf2-centered patent search, we focused primarily on patents relevant to autoimmune diseases, all the more so as they actually turned out to constitute a highly enriched topic among the patent search results.…”
Section: Introductionmentioning
confidence: 99%